Koreografi Tari Talam Sapinggan Di Sanggar Lindang Urek Kecamatan Payakumbuh Timur - Rizka Putri Ananda; Herlinda Mansyur (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
This study aims to explain and describe the Choreography of Talam Sapinggan Dance at Sanggar Lindang Urek, East Payakumbuh District, Payakumbuh City. This research is qualitative research with descriptive method. The instrument of this study is the researcher himself. Data were collected using literature studies, observations, interviews and documentation. The steps of analyzing data are data reduction, data presentation, and conclusion drawing. Sanggar Lindang Urek creates Talam Sapinggan dance to function as a performance art and entertainment. Aspects of Talam Sapinggan dance form are movement, floor design, top design, group composition, dancers, dance accompaniment and costumes. The content aspect is the idea and atmosphere. Talam Sapinggan dance has 32 types of movements. Floor Design consists of 4 designs including: Triangle, Pentagon, Circle, and Trapezoid. Top Design consists of flat, deep, vertical, horizontal, medium, high, low, curved, contrast, low and angular. The design form of large composition groups is as follows: (1) unison or synchronous, (2) alternate or alternating intervals, (3) broken or split, (4) balanced, (5) canon or alternate. The number of dancers in the Talam Sapinggan dance consists of 7 people. The musical accompaniment uses Minang tradition music created, including: gandang tasa, talempong, gandang tambua, saluang, bansi, thamburin, and assisted by vocal dendang. Costumes already use a form of creation.